The Influence Of Marketing Mixes Competency On The Purchasing Buying Behavior Of The Car Buyers In Malaysia - Supain @ Christopher, Cyril (2008)

(untitled)
Industri automotif merupakan sektor penting di dalam menjana ekonomi Malaysia.